Perbedaan Pengaruh Metode Latihan Pliometrik Side Hop dan Barrier Hops Terhadap Kemampuan Tendangan Jauh Dalam Permainan Sepakbola Pada Atlet Putra Usia 11-13 Tahun SSB Zettle Meyer Karanganyar Tahun 2020 - Thoha Isma Pratama; Herywansyah (JURNAL ILMIAH PENJAS (Penelitian, Pendidikan dan Pengajaran), 2021)
The objectives of this study were: (1) to determine the difference in the effect of side hop and barrier hops plyometric training on the long kick ability of male athletes aged 11-13 years old SSB Zettle Meyer Karanganyar in 2020. (2) to determine which exercises had a better effect. against the long kick ability of male athletes aged 11-13 years SSB Zettle Meyer Karanganyar in 2020. The research method used was an experimental method with a pretest-protest design. The population in this study were male athletes aged 11-13 years SSB Zettle Meyer Karanganyar in 2020, totaling 30 athletes, with the sampling technique used was Total Sampling. The sample was divided into two groups, namely group 1 as many as 15 athletes, received side hop plyometric training treatment and group 2 as many as 15 athletes, received barrier hops plyometric training treatment. The data collection technique was carried out by tests and measurements using the long pass test instructions. The data analysis technique was carried out by statistical analysis using the t test at a significance level of 5%. To meet the assumptions of the research results, the analysis requirements test was carried out, namely the normality test, homogeneity test, difference test and percentage increase. Based on the results of data analysis, this study produces the following conclusions: (1) There is a significant difference in the effect between side hop and barrier hops plyometric exercises. This is evidenced by the results of the calculation of the final test for each group, namely tcount = 2.880 is greater than the t table = 2.145 with a significance level of 5%. (2) side hop plyometric exercise has a better effect than barrier hops, as seen from the results of the percentage of long kick ability which shows that group 1 is 22.19%> group 2 is 7.22%.